Kontestasi Keberagamaan Umat Hindu dan Islam Wetu Telu di Pura Lingsar Lombok Barat - Anom Kumbara, Anak Agung Ngurah; Sutrisno, Nanang (Jayapangus Press, 2024)
Each religion has a different system of theology, beliefs, religious institutions, and religious practices, in addition to having certain values in common. At the ideal level, religion is believed to be able to create order, integration, and social harmony in society. However, at the empirical level, religion often shows paradoxical phenomena as a source of disintegration and conflict triggered by differences in religious ideology and practice. The purpose of this study is to explore and understand the dynamics of the contestation between Wetu Telu Muslims and Hindus and its implications. The data collection method is carried out by observation techniques, interviews, and document studies. Data analysis was carried out qualitatively based on the social practice theory and phenomenology. This study found that the dynamics of contestation of Wetu Telu Muslims and Hindus in Lingsar Temple represent the influence of modernization and the articulations of religiosity identity in the realm of ideological superstructure, social structure, as well as economic and demographic infrastructure. The implications of this contestation include the polarization of religious practices, the strengthening of group identities, and the struggle for capital resources belonging to Lingsar Temple.